Severe metabolic alterations in liver cancer lead to ERK pathway activation and drug resistance - Nwosu, Zeribe C.; Piorońska, Weronika; Battello, Nadia; Zimmer, Andreas David; Dewidar, Bedair; Han, Mei; Pereira, Sharon; Blagojević, Biljana; Castven, Darko; Charlestin, Verodia; Holenya, Pavlo; Lochead, Julia; et al. (EBioMedicine, 2020)
Background - The extracellular signal-regulated kinase (ERK) pathway regulates cell growth, and is hyper-activated and associated with drug resistance in hepatocellular carcinoma (HCC). Metabolic pathways are profoundly dysregulated in HCC. Whether an altered metabolic state is linked to activated ERK pathway and drug response in HCC is unaddressed. - Methods - We deprived HCC cells of glutamine to induce metabolic alterations and performed various assays, including metabolomics (with 13C-glucose isotope tracing), microarray analysis, and cell proliferation assays. Glutamine-deprived cells were also treated with kinase inhibitors (e.g. Sorafenib, Erlotinib, U0126 amongst other MEK inhibitors). We performed bioinformatics analysis and stratification of HCC tumour microarrays to determine upregulated ERK gene signatures in patients. - Findings - In a subset of HCC cells, the withdrawal of glutamine triggers a severe metabolic alteration and ERK phosphorylation (pERK). This is accompanied by resistance to the anti-proliferative effect of kinase inhibitors, despite pERK inhibition. High intracellular serine is a consistent feature of an altered metabolic state and contributes to pERK induction and the kinase inhibitor resistance. Blocking the ERK pathway facilitates cell proliferation by reprogramming metabolism, notably enhancing aerobic glycolysis. We have identified 24 highly expressed ERK gene signatures that their combined expression strongly indicates a dysregulated metabolic gene network in human HCC tissues. - Interpretation - A severely compromised metabolism lead to ERK pathway induction, and primes some HCC cells to pro-survival phenotypes upon ERK pathway blockade. Our findings offer novel insights for understanding, predicting and overcoming drug resistance in liver cancer patients. - Fund - DFG, BMBF and Sino-German Cooperation Project
Gesehen am 02.07.2020